Corpus callosum atrophy associated with the degree of cognitive decline in patients with Alzheimer's dementia or mild cognitive impairment: A meta-analysis of the region of interest structural imaging studies. (April 2015) - Wang, Xu-Dong; Ren, Ming; Zhu, Min-Wei; Gao, Wen-Peng; Zhang, Jun; Shen, Hong; Lin, Zhi-Guo; Feng, Hong-Lin; Zhao, Chang-Jiu; Gao, Keming
Abstract: Individual structural neuroimaging studies of the corpus callosum (CC) in Alzheimer's disease (AD) and mild cognitive impairment (MCI) with the region of interest (ROI) analysis have yielded inconsistent findings. The aim of this study was to conduct a meta-analysis of structural imaging studies using ROI technique to measure the CC midsagittal area changes in patients with AD or MCI. Databases of PubMed, the Cochrane Library, the ISI Web of Science, and Science Direct from inception to June 2014 were searched with key words "corpus callosum" or "callosal", plus "Alzheimer's disease" or "mild cognitive impairment". Twenty-three studies with 603 patients with AD, 146 with MCI, and 638 healthy controls were included in this meta-analysis. Effect size was used to measure the difference between patients with AD or MCI and healthy controls. Significant callosal atrophy was found in MCI patients with an effect size of −0.36 (95% CI, -0.57 to −0.14; P = 0.001). The degree of the CC atrophy in mild AD was less severe than that in moderate AD with a mean effect size −0.69 (95% CI, -0.89 to −0.49) versus −0.92 (95% CI, -1.16 to −0.69), respectively. Comparing with healthy controls, patients with MCI had atrophy in the anterior portion of the CC (i.e., rostrum and genu). In contrast, patients with AD had atrophy in both anterior and posterior portions (i.e., splenium). These results suggest that callosal atrophy may be related to the degree of cognitive decline in patients with MCI and AD, and it may be used as a biomarker for patients with cognitive deficit even before meeting the criteria for AD. Highlights: Significant CC atrophy in both MCI and AD relative to healthy controls. Callosal area changes were associated with stages of cognitive decline. AD had a broader span including anterior and posterior regions. MCI had a narrower area, mainly in the anterior region. Callosal area changes may reflect the pathological progress of the cortex of AD.